PENGARUH STRETCHING EXERCISE TERHADAP PERUBAHAN KEKUATAN OTOT PADA PASIEN PASCA STROKE DI WILAYAH KERJA PUSKESMAS ANAK AIR KOTO TANGAH PADANG - Andri, Khairul; Soleha, Isfatma (Ensiklopedia of Journal, 2024)
There are 121 post-stroke patients recorded at Puskesmas Anak Air in 2023. Interviews with 8 post-stroke patients, all experienced decreased muscle strength, difficulty holding objects and difficulty moving.  The aim of this study was to determine the difference in muscle strength in post-stroke patients before and after stretching exercises were carried out in post-stroke patients in the Puskesmas Anak Air  Koto Tangah Working Area, Padang. The research used was Quasi Experiment Design research using Pre and Post Test Design. The population in this study were all post-stroke patients. The research sample consisted of 10 people in September 2023. Data was collected using interviews and observation sheets in the form of SOPs. Data analysis was carried out using the paired t-Test. The results of the research showed that the average value of muscle strength level before doing 1.90 stretching exercises and after being given stretching exercises was 4.50. The results of the paired T-test obtained P-value = 0.002. This means that there is an effect of giving stretching exercises on muscle strength in post-stroke patients. Through the leadership of the Puskesmas Anak Air, especially gerontic nurses, it is hoped that the results of this research can be used as input in providing nursing care to the elderly after stroke to increase the muscle strength of the elderly through the application of stretching exercises. Keywords: Post-Stroke, Stretching Exercise, muscle strength